ØªØ·Ø¨ÙŠÙ‚ Ù†Ù…Ø· Ø§Ù„Ø®Ø±ÙŠØ·Ø© Ø§Ù„Ø®ÙŠØ§Ù„ÙŠØ© Ù„ØªØ±Ù‚ÙŠØ© ÙÙ‡Ù… Ø§Ù„Ù†ØÙˆ "ÙƒØªØ§Ø¨ Ø§Ù„Ø¢Ø¬Ø±ÙˆÙ…ÙŠØ©" (Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØØ§Ù„Ø© ÙÙŠ Ø§Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø¨Ù…Ø¹Ù‡Ø¯ Ù„Ø§Ø±ÙŠØ¨ ØÙ†ÙŠÙØ¯Ø§ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ø¯ÙŠÙˆÙŠÙƒ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬) - Aghniyarrizqi Iara Fadhilla; Fathur Rohman (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
Nahwu or Arabic grammar is a compulsory science that must be studied in every pesantren, especially the book of al-Jurumiyah, which is a book of nahwu science that has been popular among pesantren. Because one of the requirements to be able to understand texts related to religion, whether it comes from the Qur'an or hadith or the work of scholars, by understanding Arabic grammar. The purpose of this study is to find out if with the model of Imagination Map can help improve the understanding of the book of al Ajurumiyah students Mustawa al-Ula Pesantren La Raiba Hanifida Diwek Jombang. And in the learning process is often considered less pleasant for learners. This requires teachers to implement a fun learning model. So that the teacher of Pesantren La Raiba Hanifida applies the Model map of Imagination in the learning process. The results of the research in this study is the application of the Imagination Map Model in improving the understanding of the book of al Ajurumiyah. Keywords : Implementation of the Imagination Map Model, Nahwuâ€ the book of al Ajurumiyahâ€